Gramatika Bahasa Indonesia dalam Praktik Campur Kode: Studi Kasus Rubrik Opini Jawa Pos dan Implikasinya bagi Standar Baku - Ali Manshur; Moh. Mahmud; Kadek Wirahyuni (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to analyze the patterns, forms, and functions of code mixing in the Opinion column of Jawa Pos as a discursive practice of national mass media and its implications for language standards and public literacy. The study uses a qualitative approach with a case study design, making the opinion article of Jawa Pos July 2025 edition as the unit of analysis. The method used in this study uses a qualitative design with a case study approach. Data collection techniques are: 1) collecting Opinion articles of Jawa Pos July 2025 edition for one month 2) determining the opinion column to be the object of research, 3) reading the opinion column, 4) underlining code mixing, 5) identifying the forms of code mixing. The results  show  that  code  mixing  is  dominated  by  English  nominal  words  and  phrases  that  are terminological, technocratic, and evaluative, especially on issues of literacy, education, public policy, digital economy, and global politics. Code mixing is used selectively and in a controlled manner to achieve precision of meaning, build epistemic authority, and increase the persuasiveness of arguments. These findings indicate that code-mixing in Jawa Pos opinion pieces is part of grammatical practices. It operates not only at the lexical level but also interacts with the morphological and syntactic systems of Indonesian. Furthermore, the media is not random or deviant, but rather functions as a discursive strategy that reflects the global orientation and ideology of media language. This study concludes that mass media plays a significant role in normalizing code-mixing practices while shaping public attitudes toward standard language. Therefore, an adaptive and reflective editorial policy is needed to maintain a balance between global openness and the dignity of Indonesian.